Quantitative Study of Biogas Generation Potential from Different Landfill Sites of Nepal - Bikash Adhikari; Sanjay Nath Khanal; Raju Miyan; Bijay Thapa (Waste Technology, 2015)
This research paper was study of waste composition and quantitative analysis of biogas generation potential with its recovery at Sisdole, Pokhara and Karaute Dada landfill sites (LFS) of Nepal. The waste management practice in LFS are significant deciding factors for the assessment of environmental impacts caused including the release of green house gases like methane, carbondioxide etc to the atmosphere, that could contribute significantly to global warming and climate change. The total waste disposed to Sisdole LFS, Pokhara LFS and Karaute Dada LFS are 410, 80 and 7.8 tons respectively.  The waste composition was studied onsite with waste reduction method and analyzed for their composition. The organic component of wastes was found high as 61.6%, 52.5% and 65% at Sisdole, Pokhara and Karaute Dada LFS respectively. The biogas potential at these landfill sites were 12157.78 cum, 851.99 cum and 169 cum of biogas per day in Sisdole, Pokhara and Karaute Dada LFS respectively. 4.68, 0.33 and 0.07 MW energy per day can be generated from these amounts of biogas produced in Sisdole, Pokhara and Karaute Dada LFS respectively. Proper gas collection system can be the source of income from these landfill sites and help to mitigate the adverse impact of methane that is being released from these landfill sites